SOSIALISASI TRANSFORMASI BUDAYA ORGANISASI UNTUK MENINGKATKAN PROFESIONALISME DALAM PELAYANAN PUBLIK DI KANTOR DISTRIK SENTANI KABUPATEN JAYAPURA - Nur Aedah; Agustina Ivonne Poli (Bajang Institute, 2024)
The purpose of this community service activity is to improve professionalism in public services through the socialization of organizational culture transformation in Sentani District Office, Jayapura Regency. This socialization is designed to introduce the values of professionalism and integrate local culture in an effort to improve the quality of public services. The implementation method involved a participatory approach with an initial needs analysis, followed by seminars, workshops, case-based simulations, and focus group discussions. Materials delivered included an understanding of adaptive organizational culture, professionalism, and the relevance of local culture. Evaluation using questionnaires and qualitative analysis ensured the effectiveness of the activities. The implementation results showed an increase in participants' understanding of the concepts of organizational culture and professionalism. As many as 85% of participants felt more prepared to apply the values of professionalism in their daily work. Service simulations helped participants understand the application of professionalism in real situations, such as handling public complaints with empathy. Group discussions resulted in strategic recommendations, including continuous training and the establishment of a regular evaluation system. The activity identified challenges such as resistance to change and limited resources, which can be overcome through synergy with local government and communities